2020
DOI: 10.1101/2020.12.18.423483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-type specific analysis of physiological action of estrogen in mouse oviducts

Abstract: One of the endogenous estrogens, 17β-estradiol (E2) is a female steroid hormone secreted from the ovary. It is well established that E2 causes biochemical and histological changes in the uterus. The oviduct response to E2 is virtually unknown in an in vivo environment. In this study, we assessed the effect of E2 on each oviductal cell type, using an ovariectomized-hormone-replacement mouse model, single cell RNA-sequencing (scRNA-seq), in situ hybridization, and cell-type-specific deletion in mice. We found th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Therefore, Rosa-DTA model used in our study uncovers new roles of Amhr2 + mesenchyme in patterning the epithelial lumen and promoting smooth muscle differentiation. Multiple single cell RNA transcriptomic studies have identified mesenchymal subpopulations and their specific markers in the developing and adult uterus (Kirkwood et al, 2021; Mucenski et al, 2019; Saatcioglu et al, 2019) and in the adult oviduct (Ford et al, 2021; McGlade et al, 2021). With the availabilities of Cre or CreER under the control of marker gene promoters, subpopulation-specific cellular ablation studies can be feasible and potentially provide insights into their specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Rosa-DTA model used in our study uncovers new roles of Amhr2 + mesenchyme in patterning the epithelial lumen and promoting smooth muscle differentiation. Multiple single cell RNA transcriptomic studies have identified mesenchymal subpopulations and their specific markers in the developing and adult uterus (Kirkwood et al, 2021; Mucenski et al, 2019; Saatcioglu et al, 2019) and in the adult oviduct (Ford et al, 2021; McGlade et al, 2021). With the availabilities of Cre or CreER under the control of marker gene promoters, subpopulation-specific cellular ablation studies can be feasible and potentially provide insights into their specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, single-cell technique was adopted to analyze the heterogeneity, locus differentiation and ligand receptor pairs in the infundibulum, ampulla and isthmus of the oviduct in yaks. At present, there are few studies on the oviduct using single-cell technology, but some results demonstrate that E 2 shows differential expression in the transcription pro le of mouse oviduct ciliated cells and secretory cells [24], and there are differences in the differentiation of mouse epithelial cells at the distal and proximal end of the oviduct [25]. In the above studies, detailed researches on the three parts of the oviduct were not carried out.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insulin-like growth factor 1 (IGF1) was de ned as the target gene of the oviduct by mouse E 2 after single-cell RNA sequencing. Beyond that, E 2 can regulate epithelial, stromal, and muscle cells of the oviduct [24].…”
Section: Introductionmentioning
confidence: 99%